The religious origins of American freedom and equality : a response to John Rawls - Peddle, David, 1965- (Lexington Books, 2014)
The Religious Origins of American Freedom and Equality provides a compelling contribution to the discussion of the separation of church and state. Showing how the principles of freedom and equality on which separation is based have a religious origin, this book provides a vivid alternative to the construction of public reason in John Rawls's Political Liberalism.